FAKTOR-FAKTOR YANG MEMPENGARUHI PERMINTAAN PETANI JAWA BARAT TERHADAP LAHAN - Rasmikayati, Elly; Wiyono, Sulistyodewi Nur; Saefudin, Bobby Rachmat (Fakultas Pertanian, Universitas Janabadra, 2024)
Agricultural land is an important production factor in agriculture, but there is an imbalance between the availability of land and the number of land-using farmers and smallholders in West Java, which indicates that there is farmer demand for agricultural land. The objects of this research were 500 potato farmers in West Java. These respondents were selected using a 2-stage stratified sampling technique. The data used in the research are primary and secondary data. The primary data collection tool in this research is a survey. The aim of this research is to examine the factors that influence farmers' demand for agricultural land in West Java. In this study, the results obtained were that the productivity factor and market choice had a positive influence on farming profits with values of 0.59 and 0.23 respectively, then the farming profit factor had a negative influence of -0.07 and the area of land that had irrigation and The access to credit factor each has a positive influence of 0.07 on the farmer participation factor in the land market. Keywords: Agricultural Land, Farmers, Land INTISARILahan pertanian merupakan faktor produksi yang penting dalam pertanian namun terjadi ketimpangan antara ketersedian lahan dengan jumlah petani pengguna lahan dan petani gurem di Jawa Barat yang mengindikasikan adanya permintaan petani terhadap lahan pertanian. Objek pada penelitian ini adalah 500 Petani kentang di Jawa Barat, responden tersebut dipilih menggunakan teknik sampling stratifikasi 2 tahap. Data yang digunakan dalam penelitian adalah data primer dan sekunder. Alat pengumpulan data primer pada penelitian ini adalah survey. Tujuan dari penelitian ini adalah meneliti faktor-faktor yang mempengaruhi permintaan petani terhadap lahan pertanian di Jawa Barat. Pada penelitian ini diperoleh hasil faktor produktivitas dan pilihan pasar memiliki pengaruh positif terhadap keuntungan usahatani dengan nilai masing-masing sebesar 0,59 dan 0,23, kemudian faktor keuntungan usahatani memiliki pengaruh negatif sebesar -0,07 dan faktor luas lahan yang memiliki irigasi serta faktor akses terhadap kredit masing-masing memiliki pengaruh positif sebesar 0,07 terhadap faktor partisipasi petani di pasar lahan. Kata kunci: Lahan Pertanian, Petani, Lahan